Mining Rules for Head Injury Patients Using Fuzzy Taxonomic Structures - Arora, Praveen (Research Highlights in Disease and Health Research Vol. 5, 2023)
The paper discusses how to extract rules from databases that contain imprecise taxonomic structures. While previous studies have looked at extracting rules from multiple tables with fuzzy data, there hasn't been much research done specifically in the healthcare sector. The paper introduces a new algorithm that builds upon previous research and is tailored to the healthcare industry. To test the algorithm's effectiveness, it was applied to a sample dataset of patients who underwent brain surgery and fell into a coma. By analyzing the data using the algorithm, the study was able to gain important insights into the patients' conditions. When diagnosing patients, doctors rely on information from various sources, which can have their own limitations and uncertainties. Therefore, it's crucial for physicians to weigh all the available information carefully to make the most accurate diagnosis possible. The algorithm discovered in this study could be helpful in identifying potential risk factors or developing more effective treatment protocols for similar cases in the future.